Solid electrolyte coated porous microcrystalline graphite composite material, composite negative electrode and preparation method and application of composite negative electrode

By covering the microcrystalline graphite with different particle sizes, the problem of insufficient pore structure of the microcrystalline graphite is solved, the charging and discharging efficiency and cycle stability of the battery are improved, and the safety of the battery is enhanced.

CN119315013AActive Publication Date: 2025-01-14SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD

Patent Information

Application Number
CN202411500292.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-14
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

In the prior art, the pore structure of microcrystalline graphite is not rich and cannot provide sufficient space for lithium metal deposition, resulting in reduced battery capacity and insufficient cycle stability.

Method used

The porous microcrystalline graphite composite material is coated with solid electrolytes, and the inorganic solid electrolyte with different particle sizes is filled and coated, the contact area between the electrode and the electrolyte is increased, the lithium ion transmission channel is optimized, the interface polarization is reduced, and the charging and discharging efficiency of the battery is improved. .

Benefits of technology

It improves the charging and discharging efficiency of the battery, extends the service life of the battery, reduces expansion, and enhances the cycling performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315013A_ABST
    Figure CN119315013A_ABST
Patent Text Reader

Abstract

The invention discloses a solid electrolyte coated porous microcrystalline graphite composite material, a composite negative electrode and a preparation method and application of the composite negative electrode. The solid electrolyte coated porous microcrystalline graphite composite material comprises porous microcrystalline graphite with a porous structure; the particle size compounded inorganic solid electrolyte comprises a gathering part filled in a porous structure, and coating parts distributed among particles of porous microcrystalline graphite and on the surface of the porous microcrystalline graphite. The composite negative electrode comprises a current collector, a solid electrolyte coated porous microcrystalline graphite composite material arranged on the surface of the current collector and metal compounded on the surface of the composite material. The surface of the porous microcrystalline graphite is coated with the compounded solid electrolyte with different particle sizes, so that the ionic conductivity of the material can be greatly improved, and uniform deposition and dissolution of metal are facilitated; and the prepared composite negative electrode has lower expansion, the porous microcrystalline graphite can contribute higher reversible capacity, and the composite negative electrode has the advantages of high capacity and high compaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials, and in particular to a solid electrolyte-coated porous microcrystalline graphite composite material and a preparation method thereof, a novel composite negative electrode and a preparation method and application thereof. Background Art

[0002] With the rapid development of electric vehicles and portable electronic devices, the market demand for high energy density batteries is growing. Lithium metal has an extremely high theoretical specific capacity (3860 mAh / g) and the lowest electrochemical potential (-3.04 V), which makes it an ideal negative electrode material for achieving high energy density batteries. However, lithium metal easily forms lithium dendrites during the charge and discharge process, which not only reduces the capacity of the battery, but may also pierce the separator, causing the battery to short-circuit or even catch fire and explode.

[0003] Microcrystalline graphite has a high theoretical specific capacity and excellent charge and discharge performance due to its high degree of graphitization and porous structure, and has potential advantages in improving battery energy density. In addition, microcrystalline graphite has a small volume expansion, which helps maintain the stability of the battery structure during the charge and discharge process, reduces material breakage and electrode peeling caused by volume expansion, thereby improving the cycle stability of the battery and extending the battery life.

[0004] Patent CN114180568A discloses a method for pretreating microcrystalline graphite, wherein the microcrystalline graphite is pre-calcined in an atmosphere containing ammonia for a first stage, and then calcined in an atmosphere containing magnesium vapor for a second stage to obtain pretreated microcrystalline graphite. The microcrystalline graphite has the characteristics of high specific capacity, long cycle life, and good rate performance, but the microcrystalline graphite obtained by the pretreatment has a low processing temperature and its pore structure is not rich, and cannot provide rich space for lithium metal deposition. Summary of the invention

[0005] The main purpose of the present invention is to provide a solid electrolyte coated porous microcrystalline graphite composite material and a preparation method thereof, so as to overcome the deficiencies in the prior art.

[0006] Another object of the present invention is to provide a novel composite negative electrode and a preparation method thereof.

[0007] Another object of the present invention is to provide applications of the novel composite negative electrode.

[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The embodiment of the present invention provides a solid electrolyte-coated porous microcrystalline graphite composite material, which includes: Porous microcrystalline graphite, having a porous structure, the porous structure comprising mesopores and macropores, and at least part of the pores in the porous structure are connected to the outside; An inorganic solid electrolyte with a composite particle size includes an agglomeration portion filled in the porous structure, and a coating portion distributed between the particles of porous microcrystalline graphite and on the surface of the porous microcrystalline graphite, wherein the coating portion is at least used to close at least part of the pores in the porous structure so as to isolate the agglomeration portion distributed in the pores from the outside world; the agglomeration portion includes at least first inorganic solid electrolyte particles with a first particle size, and the coating portion includes at least second inorganic solid electrolyte particles with a second particle size, wherein the first particle size is smaller than the second particle size.

[0009] In some embodiments, the mass ratio of the second inorganic solid electrolyte particles to the first inorganic solid electrolyte particles in the inorganic solid electrolyte with composite particle sizes is 1:1 to 1:10.

[0010] The embodiment of the present invention also provides a method for preparing a solid electrolyte-coated porous microcrystalline graphite composite material, which comprises: The porous microcrystalline graphite is first mixed with first inorganic solid electrolyte particles having a first particle size, so that the first inorganic solid electrolyte particles are at least filled in the porous structure of the porous microcrystalline graphite to obtain a first inorganic solid electrolyte particle / porous microcrystalline graphite composite material, and then second inorganic solid electrolyte particles having a second particle size are added, so that the second inorganic solid electrolyte particles are at least distributed between the porous microcrystalline graphite particles and on the surface of the porous microcrystalline graphite to form a coating portion, thereby obtaining a solid electrolyte-coated porous microcrystalline graphite composite material.

[0011] The embodiment of the present invention also provides a solid electrolyte-coated porous microcrystalline graphite composite material prepared by the above-mentioned preparation method.

[0012] The embodiment of the present invention also provides the use of the aforementioned solid electrolyte coated porous microcrystalline graphite composite material in the preparation of a negative electrode or a metal battery.

[0013] Accordingly, an embodiment of the present invention further provides a composite negative electrode, which includes: current collector; A solid electrolyte coated porous microcrystalline graphite composite material disposed on the surface of the current collector; The metal is compounded on the surface of the solid electrolyte-coated porous microcrystalline graphite composite material.

[0014] Furthermore, an embodiment of the present invention also provides a method for preparing the aforementioned composite negative electrode, which comprises: Applying a slurry comprising a solid electrolyte coated porous microcrystalline graphite composite material, a binder, a conductive agent, and a solvent to a current collector, and drying the slurry to obtain a solid electrolyte coated porous microcrystalline graphite composite material / current collector composite structure; The solid electrolyte-coated porous microcrystalline graphite composite material / current collector composite structure is composited with a metal to obtain a composite negative electrode.

[0015] Furthermore, an embodiment of the present invention also provides a metal battery, which includes the solid electrolyte coated porous microcrystalline graphite composite material or composite electrode.

[0016] Compared with the prior art, the beneficial effects of the present invention include at least: 1) The solid electrolyte coated porous microcrystalline graphite composite material provided by the present invention adopts inorganic solid electrolytes of different particle sizes to fill and coat the porous microcrystalline graphite, which can increase the contact area between the electrode and the electrolyte, improve the physical contact of the interface, and contribute to the efficient transmission of electrons and ions. At the same time, the particle size compounding can optimize the lithium ion transmission channel in the solid electrolyte, reduce the pores between the porous microcrystalline graphite materials, improve the ion mobility, reduce the interface polarization, and improve the battery's charge and discharge efficiency. In addition, because the inorganic solid electrolyte will react with the metal to form a solid electrolyte interface layer, the particle size compounding can make the generated interface layer more uniform, stabilize the electrode structure, and avoid the shedding of active substances due to structural damage during the charge and discharge process, which affects the battery's cycle performance and safety; 2) Compared with traditional graphite materials, the composite electrode made of the solid electrolyte coated porous microcrystalline graphite composite material provided by the present invention has lower expansion. Compared with the porous carbon composite metal lithium negative electrode, the porous microcrystalline graphite itself can contribute higher reversible capacity and has the advantages of high capacity and high compaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 It is a schematic diagram of the preparation process of a solid electrolyte-coated porous microcrystalline graphite composite material in a typical embodiment of the present invention; Figure 2a It is a schematic structural diagram of a solid electrolyte-coated porous microcrystalline graphite composite material in a typical embodiment of the present invention; Figure 2b is the morphology of the original porous microcrystalline graphite; Figure 3 is a cross-sectional SEM image of the microcrystalline graphite powder after pulverization in Example 1 of the present invention; Figure 4is a cross-sectional SEM image of the porous microcrystalline graphite obtained after acid treatment in Example 1 of the present invention; Figure 5 is a cycle performance diagram of a full battery assembled with a metal negative electrode prepared in Example 2 of the present invention; Figure 6 is a cycle performance diagram of a full battery assembled with a metal negative electrode prepared in Example 4 of the present invention; Figure 7 This is a cycle performance diagram of the full battery assembled with the metal negative electrode prepared in Example 3. DETAILED DESCRIPTION

[0019] In view of the problems existing in the above-mentioned prior art, after long-term research and a large number of experiments, the inventor of this case proposed this technical solution, which mainly uses low-cost microcrystalline graphite (earthy graphite) as raw material, preferably uses high-temperature purification method to remove impurities in the graphite, and uses the pores formed after the impurities are removed to perform in-situ pore creation on the microcrystalline graphite material, and then fills and coats the pores and surface of the porous microcrystalline graphite with a solid electrolyte with a composite particle size to obtain a porous microcrystalline graphite composite material coated with an inorganic solid electrolyte, and further prepares a composite metal electrode with the advantages of high capacity and high compaction.

[0020] The technical solution, its implementation process and principle will be further explained as follows.

[0021] As one aspect of the technical solution of the present invention, a solid electrolyte-coated porous microcrystalline graphite composite material includes: Porous microcrystalline graphite, having a porous structure, the porous structure comprising mesopores and macropores, and at least part of the pores in the porous structure are connected to the outside; An inorganic solid electrolyte with a composite particle size includes an agglomeration portion filled in the porous structure, and a coating portion distributed between the particles of porous microcrystalline graphite and on the surface of the porous microcrystalline graphite, wherein the coating portion is at least used to close at least part of the pores in the porous structure so as to isolate the agglomeration portion distributed in the pores from the outside world; the agglomeration portion includes at least first inorganic solid electrolyte particles with a first particle size, and the coating portion includes at least second inorganic solid electrolyte particles with a second particle size, and the first particle size is smaller than the second particle size.

[0022] In some embodiments, the aggregation portion includes first inorganic solid electrolyte particles and second inorganic solid electrolyte particles, and the content of the first inorganic solid electrolyte particles in the aggregation portion is greater than the content of the second inorganic solid electrolyte particles.

[0023] In some more preferred embodiments, the content of the first inorganic solid electrolyte particles in the aggregation portion is more than 50% of the total mass of the inorganic solid electrolyte (i.e., a small amount of the second inorganic solid electrolyte with a smaller particle size will also be distributed in the aggregation portion). In the present invention, the first inorganic solid electrolyte particles (i.e., small-particle-size inorganic solid electrolyte particles) are easier to penetrate and fill in the small pores of the porous structure due to their smaller particle size, especially during wet mixing, because the small particle size is subject to small fluid dynamic resistance and strong diffusion ability, and it is easier to enter the pores; when the pores of the porous microcrystalline graphite and the particle size of the small-particle-size inorganic solid electrolyte particles are close, they are more preferentially entered into the pores of the porous structure. Furthermore, the first inorganic solid electrolyte particles are non-uniformly distributed in the porous structure, and their enrichment positions are mainly related to the distribution of the pore structure inside the microcrystalline graphite, and the pore structure is more densely distributed in places with rich pores.

[0024] In some embodiments, the coating includes a second inorganic solid electrolyte particle content greater than the first inorganic solid electrolyte particle content, that is, both large and small particles are present, and large particles are mainly present. Small-sized inorganic solid electrolyte particles may partially exist in the coating layer, because of physical adsorption or chemical adsorption when the inorganic solid electrolyte and porous microcrystalline graphite are mixed, and there may be smaller pores in the microcrystalline graphite, resulting in some small-sized inorganic solid electrolyte particles existing in the coating layer.

[0025] In some more preferred embodiments, the content of the second inorganic solid electrolyte particles in the coating portion is greater than 10% and less than 50% of the total mass of the inorganic solid electrolyte.

[0026] In some more preferred embodiments, in the solid electrolyte coated porous microcrystalline graphite composite material, since the first inorganic solid electrolyte particles (i.e., small-size inorganic solid electrolyte particles) are preferentially dispersed in the internal micropores of the porous microcrystalline graphite, the ideal situation is that all of the first inorganic solid electrolyte particles are filled in the porous structure to form an aggregation portion, while all of the second inorganic solid electrolyte particles (i.e., large-size inorganic solid electrolyte particles) are distributed between the porous microcrystalline graphite and coated on its surface to form a coating portion.

[0027] In some embodiments, the thickness of the coating layer coated on the surface of the porous microcrystalline graphite is 1 μm to 5 μm (close to the D of the large-particle inorganic solid electrolyte). 50 ).

[0028] In some embodiments, the composite mass ratio of the second inorganic solid electrolyte particles to the first inorganic solid electrolyte particles in the particle size composite inorganic solid electrolyte is 1:1~1:10, preferably 1:1~1:5. For example, the mass ratio of the two can be specifically 1:1, 1:2, 2:3, 2:5, 1:4, 1:5, etc., but is not limited to this.

[0029] In some embodiments, the material of the inorganic solid electrolyte with a particle size composite is an inorganic solid electrolyte, which can specifically include any one or more combinations of LATP, LLZO, LLTO, NZSP, etc., preferably LATP, whose chemical formula is Li 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0030] In some embodiments, the particle size D of the inorganic solid electrolyte with a particle size compound is 50 100nm~5μm.

[0031] Wherein, the first particle size D of the first inorganic solid electrolyte particle is 50 The particle size (ie, the small particle size) is 200 nm to 2 μm, preferably 200 nm to 1 μm, for example, it may be 200 nm, 300 nm, 600 nm, 1 μm, etc., but is not limited thereto.

[0032] Furthermore, the second particle size D of the second inorganic solid electrolyte particles is 50 The particle size (i.e., the largest particle size) is 2 μm to 5 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, etc., but is not limited thereto.

[0033] In some embodiments, the particle size D of the porous microcrystalline graphite 50 The thickness is 1 μm to 50 μm, preferably 4 μm to 20 μm.

[0034] In some embodiments, the specific surface area of ​​the porous microcrystalline graphite is 1 to 100 m 2 / g, preferably 1~60 m 2 / g.

[0035] In some embodiments, the porous microcrystalline graphite has a degree of graphitization of ≤90%.

[0036] In some embodiments, the tap density of the porous microcrystalline graphite is 0.5 g / cm 3 ~1.5g / cm 3 .

[0037] In some embodiments, the mass ratio of the inorganic solid electrolyte with composite particle size to the porous microcrystalline graphite is 1:2 to 1:30.

[0038] In some embodiments, the particle size of the solid electrolyte-coated porous microcrystalline graphite composite material is 1 μm to 52 μm, preferably 5 μm to 30 μm.

[0039] In some embodiments, the specific surface area of ​​the solid electrolyte-coated porous microcrystalline graphite composite material is 1 to 20 m 2 / g.

[0040] In some embodiments, the pore size of the solid electrolyte-coated porous microcrystalline graphite composite material is 10 to 50 nm.

[0041] In the particle size compounded solid electrolyte coated porous microcrystalline graphite composite material of the present invention, the porous microcrystalline graphite material has the characteristics of small specific surface area, rich mesopores and macropores, and the mesopores and macropores are mainly distributed inside the microcrystalline graphite. After being coated by the particle size compounded inorganic solid electrolyte, the specific surface area of ​​the porous microcrystalline graphite material is reduced, and the external pores contain uniformly dispersed solid electrolyte particles. After coating, it can be ensured that the porous microcrystalline graphite material particles are filled with solid electrolytes of different particle sizes. Due to the different particle sizes of the inorganic solid electrolyte, the contact area between the electrode and the electrolyte can be increased after compounding, the physical contact of the interface is improved, and the efficient transmission of electrons and ions is facilitated. At the same time, the lithium ion transmission channel in the solid electrolyte can be optimized by particle size compounding, the pores between the porous microcrystalline graphite materials can be reduced, the ion mobility can be improved, the interface polarization can be reduced, and the charge and discharge efficiency of the battery can be improved. In addition, since inorganic solid electrolytes react with lithium metal or sodium metal to form a solid electrolyte interface layer, the particle size compounding can make the generated interface layer more uniform, stabilize the electrode structure, and avoid the loss of active substances due to structural damage during the charge and discharge process, affecting the battery's cycle performance and safety.

[0042] As another aspect of the technical solution of the present invention, a method for preparing a solid electrolyte-coated porous microcrystalline graphite composite material includes: The porous microcrystalline graphite is first mixed with first inorganic solid electrolyte particles having a first particle size, so that the first inorganic solid electrolyte particles are at least filled in the porous structure of the porous microcrystalline graphite to obtain a first inorganic solid electrolyte particle / porous microcrystalline graphite composite material, and then second inorganic solid electrolyte particles having a second particle size are added, so that the second inorganic solid electrolyte particles are at least distributed between the porous microcrystalline graphite particles and on the surface of the porous microcrystalline graphite to form a coating portion, thereby obtaining a solid electrolyte-coated porous microcrystalline graphite composite material.

[0043] In the preparation method of the present invention, the porous microcrystalline graphite and the first inorganic solid electrolyte particles with a small particle size are first mixed, which can preferentially ensure that the first inorganic solid electrolyte particles with a small particle size enter the pores of the porous microcrystalline graphite; if the second inorganic solid electrolyte particles with a large particle size are first mixed, the pores of the porous microcrystalline graphite may be blocked, resulting in the solid electrolyte particles agglomerating into large blocks when mixed with the first inorganic solid electrolyte particles with a small particle size.

[0044] The present invention coats the surface of microcrystalline graphite with an inorganic solid electrolyte, which can greatly improve the ion conductivity of the material and is beneficial to the uniform deposition and dissolution of metallic lithium or sodium.

[0045] In some embodiments, the ratio of the sum of the mass of the first inorganic solid electrolyte particles and the second inorganic solid electrolyte particles to the mass of the porous microcrystalline graphite is 1:2 to 1:30.

[0046] In some embodiments, the composite mass ratio of the second inorganic solid electrolyte particles to the first inorganic solid electrolyte particles is 1:1 to 1:10.

[0047] In some embodiments, in the preparation method, the porous microcrystalline graphite is mixed with the first inorganic solid electrolyte particles or the second inorganic solid electrolyte particles by at least any one of direct mixing, VC mixing, wet mixing, ball milling, air flow mixing, etc., but is not limited thereto.

[0048] In some more preferred embodiments, the solvent used in the wet mixing may include at least any one of water, ethanol, acetone, formic acid, NMP, etc., more preferably ethanol or water, but not limited thereto.

[0049] In some more preferred embodiments, a dispersant is further added during the wet mixing, and the dispersant may include at least any one of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate, Tween 80, sodium hydroxyethyl cellulose, sodium citrate, etc., but is not limited thereto.

[0050] In some embodiments, the method for preparing the porous microcrystalline graphite comprises: Crushing and pulverizing the low-graphitization microcrystalline graphite ore to obtain microcrystalline graphite particles; In-situ pore formation is performed on the microcrystalline graphite particles to obtain porous microcrystalline graphite.

[0051] Wherein, the median particle size of the microcrystalline graphite particles is 1 μm to 20 μm.

[0052] In some more preferred embodiments, the in situ pore creation method comprises at least one of high temperature purification and chemical purification.

[0053] In some more preferred embodiments, the method for preparing the porous microcrystalline graphite specifically comprises: The raw microcrystalline graphite with low graphitization degree is crushed and pulverized, and finally the material is pulverized to a median particle size of 1 μm-20 μm, and sieved through a 325-mesh sieve; the pulverizing equipment can be one or a combination of at least multiple of a ball mill, a jet mill, a mechanical pulverizer, a roller mill, a sand mill, etc.; The above-mentioned crushed materials need to be purified by high temperature or chemical purification, or a combination of the two, to perform in-situ pore formation.

[0054] In some more preferred embodiments, the high-temperature purification method comprises: placing microcrystalline graphite particles in a graphitization device, heating them at a high temperature, and performing the in-situ pore formation.

[0055] Furthermore, the high-temperature purification method may specifically include: putting the crushed material into a graphitization furnace, and heating the material at a certain heating rate.

[0056] Furthermore, the heating rate is 1°C / min to 10°C / min, for example, it can be 1°C / min, 2°C / min, 5°C / min, 10°C / min, etc. The heating temperature is above 1800°C, preferably the temperature is controlled at 2200°C to 2500°C, the heating time is 1h to 20h, and the preferred heating time is 1h to 6h. The high-temperature purification is carried out in a protective atmosphere, and the protective atmosphere is formed by one or both of nitrogen and argon.

[0057] Furthermore, the graphitization device (i.e., graphitization furnace) may include any one of an Acheson graphitization furnace, a series graphitization furnace, a vacuum graphitization furnace, a continuous graphitization furnace, a box-type graphitization furnace, a Kastner furnace, etc., but is not limited thereto.

[0058] In some more preferred embodiments, the chemical purification method comprises: mixing microcrystalline graphite particles, an acid solution or an alkaline solution, and performing the in-situ pore creation.

[0059] Furthermore, the mass ratio of the microcrystalline graphite particles to the acid solution or the alkaline solution is 1:3-10.

[0060] Furthermore, the mixing time is 0.5 to 24 hours.

[0061] Furthermore, the chemical purification method may specifically include: mixing microcrystalline graphite particles (i.e., the crushed material obtained above), acid solution or alkaline solution in a certain mass ratio (1:3~10), stirring for 0.5~24h, solid-liquid separation, washing with pure water to pH=4~8, and drying.

[0062] Furthermore, the acid contained in the acid solution may include any one or a combination of two or more of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid, sulfuric acid, etc., but is not limited thereto. The acid content in the acid solution is 5 wt% to 40 wt%.

[0063] Furthermore, the alkali contained in the alkaline solution includes any one or a combination of two of potassium hydroxide, sodium hydroxide, etc., but is not limited thereto. The concentration of the alkaline solution is 1 mol / L to 6 mol / L.

[0064] As a more preferred embodiment, please refer to Figure 1 As shown, the preparation method of a solid electrolyte coated porous microcrystalline graphite composite material of the present invention adopts chemical purification and high temperature purification at the same time, and specifically comprises the following steps: The raw material of microcrystalline graphite with low graphitization degree is crushed and sieved to retain the undersize material. The undersize material is mixed with an acid solution / alkaline solution and stirred, and chemically purified to obtain pre-treated microcrystalline graphite. The pre-treated microcrystalline graphite is further subjected to in-situ high-temperature purification to obtain porous microcrystalline graphite. The porous microcrystalline graphite is mixed with first inorganic solid electrolyte particles having a first particle size (i.e., small particle size) to obtain first inorganic solid electrolyte-doped porous microcrystalline graphite, and then the first inorganic solid electrolyte-doped porous microcrystalline graphite is mixed with second inorganic solid electrolyte particles having a second particle size (i.e., large particle size) to obtain a large and small particle size composite material of solid electrolyte-coated porous microcrystalline graphite, whose structure is as follows: Figure 2a As shown, the yellow color represents solid electrolyte particles, while the morphology of the original porous microcrystalline graphite is as follows Figure 2b shown.

[0065] In summary, the present invention uses low-cost microcrystalline graphite (earthy graphite) as raw material, preferably low-grade, high-impurity ore (graphitization degree less than 90%) with lower cost, preferably high-temperature purification method to remove impurities in the graphite, and uses the pores formed after the impurities are removed to perform in-situ pore formation on the microcrystalline graphite material. Compared with conventional porous carbon, the porous microcrystalline graphite has a higher degree of graphitization, the carbon material itself has a high reversible capacity, a high initial efficiency, and a lower cost, which has great advantages.

[0066] As another aspect of the technical solution of the present invention, it also relates to the use of the solid electrolyte coated porous microcrystalline graphite composite material in the preparation of negative electrodes or metal batteries.

[0067] Furthermore, another aspect of the embodiment of the present invention also provides a composite negative electrode, which includes: current collector; A solid electrolyte coated porous microcrystalline graphite composite material disposed on the surface of the current collector; The metal is compounded on the surface of the solid electrolyte-coated porous microcrystalline graphite composite material.

[0068] The metal may be any one of lithium and sodium, but is not limited thereto.

[0069] In some embodiments, the compaction density of the composite negative electrode is 1 g / cm 3 ~2.5g / cm 3 .

[0070] Compared with the use of traditional graphite materials, the composite negative electrode composed of the aforementioned solid electrolyte coated porous microcrystalline graphite composite material of the present invention has lower expansion. And compared with the porous carbon composite metal lithium negative electrode, the porous microcrystalline graphite itself can contribute higher reversible capacity, and has the advantages of high capacity and high compaction.

[0071] Another aspect of the embodiments of the present invention further provides a method for preparing the composite negative electrode, which comprises: Applying a slurry comprising a solid electrolyte coated porous microcrystalline graphite composite material, a binder, a conductive agent, and a solvent to a current collector, and drying the slurry to obtain a solid electrolyte coated porous microcrystalline graphite composite material / current collector composite structure; The solid electrolyte is coated with a porous microcrystalline graphite composite material / current collector composite structure and composited with a metal to obtain a composite negative electrode.

[0072] In some embodiments, the slurry is applied to the current collector to a thickness of 40 μm to 60 μm.

[0073] In some embodiments, the solid electrolyte-coated porous microcrystalline graphite composite material (ie, inorganic solid electrolyte and porous microcrystalline graphite with mixed particle sizes) accounts for 60 wt% to 95 wt% of the solid matter in the slurry.

[0074] Furthermore, the solid content of the slurry is 8% to 20%, preferably 10%, 11%, 12% or 13%.

[0075] In some embodiments, the binder in the slurry may include any one or a combination of two or more of polyvinylidene fluoride, polyacrylic acid, polyamide, LA133 (aqueous dispersion of acrylonitrile multipolymer), polyvinyl alcohol, polyethyleneimine, polyimide, polyethylene, SBR (styrene-butadiene latex), carboxymethyl cellulose, etc., but is not limited thereto.

[0076] Furthermore, the binder accounts for 1wt% to 10wt% of the solid matter in the slurry.

[0077] In some embodiments, the conductive agent may include any one or a combination of two or more of SP (conductive carbon black), graphite, acetylene black, carbon nanotubes, graphene, Ketjen black, etc., but is not limited thereto.

[0078] Furthermore, the conductive agent accounts for 1wt% to 10wt% of the solid matter in the slurry.

[0079] Further, the solvent may include at least any one of NMP (N-methylpyrrolidone), DMF (N,N-dimethylformamide), water, etc., but is not limited thereto.

[0080] In some embodiments, the method of compounding the solid electrolyte-coated porous microcrystalline graphite composite material / current collector composite structure with metal includes any one of cold rolling, hot rolling, calendering, extrusion, etc., but is not limited thereto.

[0081] Among them, in some more preferred embodiments, the preparation method of the composite negative electrode may specifically include the following steps: The solid electrolyte coated porous microcrystalline graphite composite material, a binder, a conductive agent, and a solvent are mixed to obtain a slurry, the slurry is coated on a current collector, and after drying, an inorganic solid electrolyte composite porous microcrystalline graphite material current collector is obtained; The porous microcrystalline graphite material current collector compounded with the inorganic solid electrolyte is compounded with lithium or sodium metal to obtain a lithium / sodium metal composite negative electrode.

[0082] Furthermore, another aspect of an embodiment of the present invention provides a metal battery, which includes the aforementioned solid electrolyte coated porous microcrystalline graphite composite material or composite electrode.

[0083] Correspondingly, the metal battery can be any one of a lithium battery and a sodium battery.

[0084] Through the above technical scheme, the present invention coats the solid electrolytes with different particle sizes on the surface of porous microcrystalline graphite, which can greatly improve the ion conductivity of the material and is conducive to the uniform deposition and dissolution of metals; and the prepared composite negative electrode has lower expansion, and the porous microcrystalline graphite itself can contribute to a higher reversible capacity, with the advantages of high capacity and high compaction.

[0085] In order to make the purpose, technical solution and application of the present invention clearer, the technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. The implementation conditions used in the following embodiments can be further adjusted according to actual needs, and the unspecified implementation conditions are usually the conditions in conventional experiments.

[0086] Example 1 The low-graphitization microcrystalline graphite raw material is crushed and pulverized to a median particle size of 1μm-20μm, sieved through a 325-mesh sieve, and the undersize is retained. A certain amount of the undersize and acid solution are mixed in a mass ratio of 1:3 and stirred for 3 hours, wherein the acid solution is a mixed solution of nitric acid and hydrochloric acid with a concentration of 15wt%. After the stirring is completed, the mixed solution is separated into solid and liquid, washed with water to neutrality, and dried to obtain the pre-treated microcrystalline graphite. The cross-sectional SEM image of the microcrystalline graphite crushed in this step is as follows Figure 3 The cross-sectional SEM image of the porous microcrystalline graphite obtained after acid treatment is shown in Figure 4 shown.

[0087] The pretreated microcrystalline graphite is placed in a graphite crucible and placed in a graphitization furnace. The temperature is first increased to 1000°C at a heating rate of 10°C / min, and then increased to 2200°C at a heating rate of 5°C / min, and kept warm for 6 hours. After the reaction is completed, it is cooled to room temperature to obtain a porous microcrystalline graphite material.

[0088] 100 g of porous microcrystalline graphite material and 10 g of small particle size (D 50 500nm) inorganic solid electrolyte LLTO was dispersed in ethanol, and 0.5g dispersant was added and stirred for 30min, then filtered, washed and dried to obtain small-particle inorganic solid electrolyte porous microcrystalline graphite material. The above-mentioned small-particle inorganic solid electrolyte porous microcrystalline graphite material and 10g large-particle inorganic solid electrolyte (D 50 4μm) LLTO is directly dry-mixed for 60min to obtain an inorganic solid electrolyte-coated porous microcrystalline graphite composite material with a composite size of particles.

[0089] The inorganic solid electrolyte coated porous microcrystalline graphite composite material with large and small particle sizes, a binder, and a conductive agent are mixed in a mass ratio of 93:2:5, and an appropriate amount of pure water is added and stirred to obtain a slurry. The slurry is coated on a current collector, and after drying, an inorganic solid electrolyte composite porous microcrystalline graphite material current collector is obtained.

[0090] The porous microcrystalline graphite material current collector compounded with the inorganic solid electrolyte is compounded with lithium metal by cold pressing to obtain a lithium metal composite negative electrode.

[0091] Example 2 This embodiment adopts the same scheme as that of embodiment 1 to prepare the lithium metal composite negative electrode, except that the small-particle inorganic solid electrolyte is replaced by 600nm LATP, and the large-particle inorganic solid electrolyte is replaced by 3μm LATP.

[0092] The cycle performance of the full battery assembled with the metal negative electrode prepared in this embodiment is as follows Figure 5 shown.

[0093] Example 3 This embodiment adopts the same scheme as that of embodiment 1 to prepare the lithium metal composite negative electrode, except that the small-particle inorganic solid electrolyte is 600nm LLZO, and the large-particle inorganic solid electrolyte is 4μm LATP.

[0094] Example 4 The same method as in Example 1 was used to prepare porous microcrystalline graphite.

[0095] 100g of porous microcrystalline graphite material and 3g of 600nm LATP were dispersed in an appropriate amount of water, and an appropriate amount of dispersant was added and stirred for 60min, and then filtered, washed and dried to obtain a small-particle-size inorganic solid electrolyte porous microcrystalline graphite material. The above-mentioned small-particle-size inorganic solid electrolyte porous microcrystalline graphite material and 2g of 3μm LATP were directly dry-mixed for 60min to obtain a composite inorganic solid electrolyte-coated porous microcrystalline graphite with a large and small particle size.

[0096] The inorganic solid electrolyte coated porous microcrystalline graphite composite material containing a particle size compound, a binder, and a conductive agent are mixed in a mass ratio of 93:2:5, and an appropriate amount of pure water is added and stirred to obtain a slurry, and the slurry is coated on a current collector, and after drying, an inorganic solid electrolyte compounded porous microcrystalline graphite material current collector is obtained.

[0097] The porous microcrystalline graphite material current collector compounded with the inorganic solid electrolyte is compounded with lithium metal by cold pressing to obtain a lithium metal composite negative electrode.

[0098] The cycle performance of the full battery assembled with the metal negative electrode prepared in this embodiment is as follows Figure 6 shown.

[0099] Example 5 The low-graphitization microcrystalline graphite raw material is crushed and pulverized to a median particle size of 1μm-20μm, sieved through a 325-mesh sieve, and the undersize is retained. A certain amount of the undersize is mixed with an alkaline solution at a mass ratio of 1:3 and stirred for 3 hours, wherein the alkaline solution is a 1mol / L NaOH solution. After the stirring is completed, the mixed solution is separated into solid and liquid, washed with water until neutral, and dried to obtain pre-treated microcrystalline graphite.

[0100] The pretreated microcrystalline graphite is placed in a graphite crucible and placed in a graphitization furnace. The temperature is first increased to 1000°C at a heating rate of 10°C / min, and then increased to 2500°C at a heating rate of 5°C / min, and kept warm for 3 hours. After the reaction is completed, it is cooled to room temperature to obtain a porous microcrystalline graphite material.

[0101] The lithium metal composite negative electrode was prepared by the same method as in Example 1, except that the small-particle inorganic solid electrolyte was 20 g 600 nm LATP, and the large-particle inorganic solid electrolyte was 4 g 3 μm LATP.

[0102] Example 6 The low-graphitization microcrystalline graphite raw material is crushed and pulverized to a median particle size of 1μm-20μm, sieved through a 325-mesh sieve, and the sieved material is retained. It is placed in a graphite crucible and placed in a graphitization furnace. The temperature is first increased to 1000℃ at a heating rate of 10℃ / min, and then increased to 2500℃ at a heating rate of 5℃ / min, and kept warm for 6 hours. After the reaction is completed, it is cooled to room temperature to obtain a porous microcrystalline graphite material.

[0103] The porous microcrystalline graphite and the solid electrolyte were compounded in the same manner as in Example 4 to obtain a lithium metal composite negative electrode.

[0104] Example 7 The porous microcrystalline graphite was prepared by the same method as in Example 1, except that no high-temperature graphitization treatment was performed.

[0105] The same scheme as in Example 2 was used to prepare a lithium metal composite negative electrode.

[0106] Example 8 The porous microcrystalline graphite and lithium metal composite negative electrode was prepared by the same method as in Example 5, except that the high temperature treatment process was: heating the temperature to 1800° C. at a heating rate of 5° C. / min and keeping the temperature for 6 h.

[0107] The small-particle inorganic solid electrolyte is 30g 1μm LATP, and the large-particle inorganic solid electrolyte is 7.5g 3μm LATP.

[0108] Example 9 This embodiment adopts the same scheme as that of Embodiment 5 to prepare the lithium metal composite negative electrode, except that the screened material and the alkaline solution are mixed in a mass ratio of 1:10.

[0109] Example 10 This embodiment adopts the same scheme as that of embodiment 5 to prepare the lithium metal composite negative electrode, except that: a certain amount of the screened material and the alkaline solution are mixed in a mass ratio of 1:3 and stirred for 0.5h.

[0110] Embodiment 11 This embodiment adopts the same scheme as that of Embodiment 5 to prepare the lithium metal composite negative electrode, except that: a certain amount of the screened material and the alkaline solution are mixed in a mass ratio of 1:3 and stirred for 24 hours.

[0111] Example 12 This embodiment adopts the same scheme as embodiment 6 to prepare the lithium metal composite negative electrode, except that: the temperature is first increased to 1000°C at a heating rate of 1°C / min, then increased to 2500°C at a heating rate of 5°C / min, and kept warm for 6 hours.

[0112] Example 13 This embodiment adopts the same scheme as that of embodiment 1 to prepare the lithium metal composite negative electrode, except that: the small-particle inorganic solid electrolyte is 30g 500nm LLTO, and the large-particle inorganic solid electrolyte is 20g 3μm LLTO.

[0113] Embodiment 14 This embodiment adopts the same scheme as that of embodiment 1 to prepare the lithium metal composite negative electrode, except that: the small-particle inorganic solid electrolyte is 2.33g 500nm LLTO, and the large-particle inorganic solid electrolyte is 1g 3μm LLTO.

[0114] Embodiment 15 This embodiment adopts the same scheme as that of Embodiment 8 to prepare the lithium metal composite negative electrode, except that: the small-particle inorganic solid electrolyte is 10g 600nm LATP, and the large-particle inorganic solid electrolyte is 1g 3μm LATP.

[0115] Comparative Example 1 The lithium metal composite negative electrode was prepared by the same scheme as in Example 1, except that the small-particle inorganic solid electrolyte was 2 g 600 nm LATP, and the large-particle inorganic solid electrolyte was 8 g 3 μm LATP.

[0116] Comparative Example 2 The lithium metal composite negative electrode was prepared by the same scheme as in Example 1, except that the small-particle inorganic solid electrolyte was 10 g 600 nm LATP, and the large-particle inorganic solid electrolyte was not used.

[0117] Comparative Example 3 The lithium metal composite negative electrode was prepared by the same scheme as in Example 1, except that the large-particle inorganic solid electrolyte was 10 g 3 μm LATP, and the small-particle inorganic solid electrolyte was not used.

[0118] The cycle performance of the full battery assembled with the metal negative electrode prepared in this comparative example is as follows Figure 7 shown.

[0119] Comparative Example 4 The lithium metal composite negative electrode was prepared by the same scheme as in Example 1, except that the porous microcrystalline graphite material was replaced by sieved undersize material, and no acid treatment and high-temperature purification were performed.

[0120] The present invention also uses a Gaobo BK300C specific surface area meter and an American Mac TriStar-3030 pore size analyzer to test the specific surface area and pore size distribution of the porous microcrystalline graphite material compounded with the inorganic solid electrolyte obtained in the above Examples 1-15 and Comparative Examples 1-4, uses a Malvern 3000 laser particle size analyzer to test the particle size range of the sample, uses a Zeiss SEM 460 thermal field emission scanning electron microscope and an Oxford Ultim Max170 spectrometer to test the morphology of the sample, uses a Blue Electric M340A test cabinet to test the electrochemical properties of the sample, and the battery assembly is carried out in a German Braun glove box.

[0121] The button-type full battery is prepared by a method known in the art: NCM polycrystalline is used as the positive electrode, the above-mentioned lithium metal composite negative electrode is used as the negative electrode, the electrolyte is a conventional carbonate, Celgard2400 is used as the separator, and the shell is a 2032 button-type battery shell, and the button-type full battery is assembled. The test conditions are: at room temperature, first use 0.1C constant rate charge and discharge for two weeks, the voltage range is 2.75-4.2V, and then use 1C / 1C charge and discharge system for cycling.

[0122] Result analysis: As shown in Table 1, the particle size and specific surface area of ​​the composite materials prepared by different purification methods, different particle sizes and different types of solid electrolytes are significantly different. In particular, when the purification method of porous microcrystalline graphite is changed from chemical purification and high-temperature purification to a single purification method, the specific surface area of ​​the obtained composite material is significantly reduced. This is because when a single purification method or no purification treatment is used, some impurities, insufficiently dispersed particles, and some closed micropores or mesopores in the microcrystalline graphite reduce the porosity, thereby affecting the specific surface area of ​​the material. From Example 1 to Example 15, the capacity retention rate of Comparative Example 4 can be seen that the capacity retention rate of the composite material with a larger specific surface area after 150 cycles is more than 80%, while the capacity retention rate of the battery assembled with the material without purification treatment is only 68.5%. This may be in the material with a smaller specific surface area. Due to the limited pore structure of the material, the ions need a longer particle size to reach the active site, which not only increases the diffusion resistance of the ions, but also may cause the interface stability between the material and the electrolyte to deteriorate, so the performance decay is obvious during the cycle. By comparing Example 5, Example 10, and Example 11, it can be seen that the amount of alkali solution and the stirring time have a certain influence on the specific surface area of ​​the material. When the amount of alkali solution is too much or the stirring time is too short, there will be problems such as impurities being difficult to remove or insufficient reaction, which will affect the pore structure and electrochemistry of the material. It can be seen from Example 8, Example 13, Example 14 and Comparative Example 1 that in addition to the treatment process of microcrystalline graphite, the amount of inorganic solid electrolyte added also has a certain influence on its cycle performance. When the amount of small-particle inorganic solid electrolyte is in a suitable range, the assembled full battery can be cycled 150 times, and when the content of small-particle inorganic solid electrolyte is less, it will cause obvious gaps between large and small particle sizes, reduce the effective transmission channel of lithium ions, and affect the lithium ion transmission rate. Secondly, due to the inappropriate ratio of large and small particle sizes, it will also affect the overall structure of the material, making the active substances not tightly connected and the utilization rate low, thereby affecting the performance of the pole piece and the battery.

[0123] Table 1 Composite materials prepared in Examples 1-15 and Comparative Examples 1-4 and full battery performance ; In addition, the inventor of this case also conducted experiments with other raw materials and conditions listed in this specification with reference to the methods of Examples 1 to 15, and also achieved the same technical effects.

[0124] It should be understood that the above are only specific application examples of the present invention and do not constitute any limitation on the protection scope of the present invention. Any technical solution formed by equivalent transformation or equivalent replacement falls within the protection scope of the present invention.

Claims

1. A solid electrolyte coated porous microcrystalline graphite composite material, characterized in that: include: Porous microcrystalline graphite, having a porous structure, the porous structure comprising mesopores and macropores, and at least part of the pores in the porous structure are connected to the outside; An inorganic solid electrolyte with a composite particle size includes an agglomeration portion filled in the porous structure, and a coating portion distributed between the particles of porous microcrystalline graphite and on the surface of the porous microcrystalline graphite, wherein the coating portion is at least used to close at least part of the pores in the porous structure to isolate the inorganic solid electrolyte distributed in the pores from the outside world; the agglomeration portion includes at least first inorganic solid electrolyte particles with a first particle size, and the coating portion includes at least second inorganic solid electrolyte particles with a second particle size, and the first particle size is smaller than the second particle size.

2. The solid electrolyte-coated porous microcrystalline graphite composite material according to claim 1, characterized in that: The agglomeration portion includes first inorganic solid electrolyte particles and second inorganic solid electrolyte particles, and the content of the first inorganic solid electrolyte particles in the agglomeration portion is greater than the content of the second inorganic solid electrolyte particles; Preferably, the content of the first inorganic solid electrolyte particles in the aggregation portion is more than 50% of the total mass of the inorganic solid electrolyte; And / or, the coating portion includes a content of the second inorganic solid electrolyte particles greater than the content of the first inorganic solid electrolyte particles; Preferably, the content of the second inorganic solid electrolyte particles in the coating portion is more than 10% and less than 50% of the total mass of the inorganic solid electrolyte; And / or, the coating portion has a thickness of 1 μm to 5 μm.

3. The solid electrolyte coated porous microcrystalline graphite composite material according to claim 1, characterized in that: The mass ratio of the second inorganic solid electrolyte particles to the first inorganic solid electrolyte particles in the inorganic solid electrolyte with a composite particle size is 1:1 to 1:10, preferably 1:1 to 1:5; And / or, the material of the inorganic solid electrolyte with composite particle size includes any one or more combinations of LATP, LLZO, LLTO, and NZSP, preferably LATP; And / or, the particle size D of the inorganic solid electrolyte with the particle size compound is 50 100nm~5μm; and / or, the first particle size D of the first inorganic solid electrolyte particles 50 200nm~2μm, preferably 200nm~1μm; and / or, the second particle size D of the second inorganic solid electrolyte particles 50 2μm~5μm; And / or, the particle size D of the porous microcrystalline graphite 50 1 μm to 50 μm, preferably 4 μm to 20 μm; And / or, the specific surface area of ​​the porous microcrystalline graphite is 1 to 100 m 2 / g, preferably 1~60 m 2 / g; And / or, the graphitization degree of the porous microcrystalline graphite is ≤90%; And / or, the tap density of the porous microcrystalline graphite is 0.5 g / cm 3 ~1.5g / cm 3 ; And / or, the mass ratio of the inorganic solid electrolyte with composite particle size to the porous microcrystalline graphite is 1:2-1:

30.

4. The solid electrolyte-coated porous microcrystalline graphite composite material according to claim 1, characterized in that: The particle size of the solid electrolyte-coated porous microcrystalline graphite composite material is 1 μm to 52 μm, preferably 5 μm to 30 μm; And / or, the specific surface area of ​​the solid electrolyte-coated porous microcrystalline graphite composite material is 1 to 20 m 2 / g; And / or, the pore size of the solid electrolyte-coated porous microcrystalline graphite composite material is 10-50 nm; And / or, in the solid electrolyte coated porous microcrystalline graphite composite material, the first inorganic solid electrolyte particles are filled in the porous structure to form an aggregation portion, and the second inorganic solid electrolyte particles are distributed between the porous microcrystalline graphite particles and on the surface of the porous microcrystalline graphite to form a coating portion.

5. The method for preparing the solid electrolyte coated porous microcrystalline graphite composite material according to any one of claims 1 to 4, characterized in that: include: The porous microcrystalline graphite is first mixed with first inorganic solid electrolyte particles having a first particle size, so that the first inorganic solid electrolyte particles are at least filled in the porous structure of the porous microcrystalline graphite to obtain a first inorganic solid electrolyte particle / porous microcrystalline graphite composite material, and then second inorganic solid electrolyte particles having a second particle size are added, so that the second inorganic solid electrolyte particles are at least distributed between the porous microcrystalline graphite particles and on the surface of the porous microcrystalline graphite to form a coating portion, thereby obtaining a solid electrolyte-coated porous microcrystalline graphite composite material.

6. The preparation method according to claim 5, characterized in that: The ratio of the sum of the mass of the first inorganic solid electrolyte particles and the second inorganic solid electrolyte particles to the mass of the porous microcrystalline graphite is 1:2 to 1:30; And / or, the mass ratio of the second inorganic solid electrolyte particles to the first inorganic solid electrolyte particles is 1:1 to 1:10; And / or, the method of mixing the porous microcrystalline graphite with the first inorganic solid electrolyte particles or the second inorganic solid electrolyte particles includes at least one of direct mixing, VC mixing, wet mixing, ball milling, and air flow mixing; Preferably, the solvent used in the wet mixing includes at least one of water, ethanol, acetone, formic acid, and NMP, more preferably ethanol or water; Preferably, a dispersant is further added during the wet mixing, and the dispersant includes at least one of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate, Tween 80, sodium hydroxyethyl cellulose, and sodium citrate; And / or, the method for preparing the porous microcrystalline graphite comprises: Crushing and pulverizing the low-graphitization microcrystalline graphite ore to obtain microcrystalline graphite particles; In-situ pore formation is performed on the microcrystalline graphite particles to obtain porous microcrystalline graphite; Preferably, the median particle size of the microcrystalline graphite particles is 1 μm to 20 μm; Preferably, the in-situ pore-forming method includes at least one of high-temperature purification and chemical purification; Particularly preferably, the high-temperature purification method comprises: placing microcrystalline graphite particles in a graphitization device, heating them by increasing the temperature, and performing the in-situ pore formation; wherein the heating rate is 1°C / min to 10°C / min, the heating temperature is above 1800°C, preferably 2200°C to 2500°C, the heating time is 1h to 20h, preferably 1h to 6h, and the high-temperature purification is performed in a protective atmosphere, and the protective atmosphere is formed by one or both of nitrogen and argon; The graphitization device includes any one of an Acheson graphitization furnace, a series graphitization furnace, a vacuum graphitization furnace, a continuous graphitization furnace, a box-type graphitization furnace, and a Kastner furnace; Particularly preferably, the chemical purification method comprises: mixing microcrystalline graphite particles, an acid solution or an alkaline solution, and performing the in-situ pore formation, wherein the mass ratio of the microcrystalline graphite particles to the acid solution or the alkaline solution is 1:3~10, and the mixing time is 0.5~24h; the acid contained in the acid solution comprises any one or a combination of two or more of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid, and sulfuric acid; the alkali contained in the alkaline solution comprises any one or a combination of two of potassium hydroxide and sodium hydroxide, the acid content in the acid solution is 5 wt%~40wt%, and the concentration of the alkaline solution is 1 mol / L~6 mol / L.

7. Use of the solid electrolyte coated porous microcrystalline graphite composite material according to any one of claims 1 to 4 in the preparation of negative electrodes or metal batteries.

8. A composite negative electrode, characterized in that: include: current collector; The solid electrolyte coated porous microcrystalline graphite composite material according to any one of claims 1 to 4 is disposed on the surface of the current collector; A metal compounded on the surface of the solid electrolyte-coated porous microcrystalline graphite composite material; Preferably, the metal includes any one of lithium and sodium; Preferably, the compaction density of the composite negative electrode is 1 g / cm 3 ~2.5g / cm 3 .

9. The method for preparing the composite negative electrode according to claim 8, characterized in that: include: Applying a slurry comprising a solid electrolyte coated porous microcrystalline graphite composite material, a binder, a conductive agent, and a solvent to a current collector, and drying the slurry to obtain a solid electrolyte coated porous microcrystalline graphite composite material / current collector composite structure; The solid electrolyte-coated porous microcrystalline graphite composite material / current collector composite structure is composited with a metal to obtain a composite negative electrode; Preferably, the thickness of the slurry applied to the current collector is 40 μm to 60 μm; Preferably, the solid electrolyte-coated porous microcrystalline graphite composite material accounts for 60wt% to 95wt% of the solid matter in the slurry. Preferably, the solid content of the slurry is 8% to 20%; Preferably, the binder includes any one or a combination of two or more of polyvinylidene fluoride, polyacrylic acid, polyamide, aqueous dispersion of acrylonitrile multipolymer, polyvinyl alcohol, polyethyleneimine, polyimide, polyethylene, styrene-butadiene latex, and carboxymethyl cellulose; Preferably, the binder accounts for 1wt% to 10wt% of the solid matter in the slurry; Preferably, the conductive agent includes any one or a combination of two or more of conductive carbon black, graphite, acetylene black, carbon nanotubes, graphene, and Ketjen black; Preferably, the conductive agent accounts for 1wt% to 10wt% of the solid matter in the slurry; Preferably, the solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide and water; Preferably, the method of compounding the solid electrolyte-coated porous microcrystalline graphite composite material / current collector composite structure with the metal includes any one of cold rolling, hot rolling, calendering and extrusion.

10. A metal battery, characterized in that: It comprises the solid electrolyte coated porous microcrystalline graphite composite material as described in any one of claims 1 to 4 or the composite electrode as described in claim 8; preferably, the metal battery comprises any one of a lithium battery and a sodium battery.

Citation Information

Patent Citations

  • Pretreated microcrystalline graphite, negative electrode active material and preparation and application of pretreated microcrystalline graphite and negative electrode active material

    CN114180568A

  • Fast-charging graphite composite material and preparation method thereof

    CN114335460A

  • Negative electrode active material, solid-state battery, and method for producing negative electrode active material

    CN115668546A

  • Electrode for all-solid-state battery, all-solid-state battery, and method for producing same

    CN116741933A

  • Positive electrode for all-solid-state secondary battery, all-solid-state secondary battery, and method for preparing same

    CN118198253A

Cited By

  • Composite porous carbon matrix material coated with solid electrolyte in situ and preparation method of composite porous carbon matrix material

    CN120955141A

  • Negative electrode material, preparation method thereof and lithium ion battery

    CN121149175A